Patterns of Population’s Self-Preservation Behavior: Research Approaches and Building Experience - Korolenko Aleksandra V. (Economic and Social Changes: Facts, Trends, Forecast, 2018)
As countries make their epidemiological transition, the contribution of behavioral risk factors to population’s health is increased; they include challenges of low physical and medical activity, diet and sleep violations, imbalance of work and rest, tobacco and alcohol consumption, and high stress loads. In Russia, the situation is complicated by incomplete epidemiological transition, as well as increased morbidity and mortality from endogenous and quasi-endogenous causes. The purpose for the article is to analyze methodological approaches to studying the self-preservation behavior and build models describing it for the population of the Vologda Oblast. Russian scholars A.I. Antonov, V.A. Borisov, I.V. Zhuravleva, L.S. Shilova, G.I., Ivakhnenko, T.V. Shushunova, and A.E. Lugovoy attempt to highlight the patterns of self-preservation behavior taking into account all or some of its elements (needs, attitudes, motives and actions), but not considering them in a single system. For constructing models the present study applied the method of decision tree using data from sociological surveys, which helps identify eight possible options. As revealed, 57% of the population in the Vologda Oblast demonstrate the strategy characterized by recognizing health as the main value, people’s concern for their health and presence of health-preserving practices. The rest demonstrate certain behavioral risks: 21% of respondents do not consider health as one of their life priorities, 15% – are not motivated to choose a healthy lifestyle, and 29% do not take any actions to preserve and improve their own health. It was established that lack of health in the system of life values, low concern for health, passive use of self-preservation measures are directly related to the spread of self-destructive practices (alcohol abuse, smoking, unhealthy diet and low physical activity). At the next stage, a survey of residents in the Vologda Oblast is planned, the results of which will help deepen the research study by a more detailed study of patterns of self-preservation behavior at the level of individual groups, expanding the range of behavioral risk factors under study